ANALISIS DUGAAN PRAKTIK ANTI PERSAINGAN PADA SISTEM EKSKLUSIVITAS PEMBAYARAN PLATFORM SHOPEE DALAM PERSPEKTIF MANAJEMEN PERBANKAN SYARIAH - Nur Syam Mario; Anugrah Syahrani; Otong Karyono (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to analyze the alleged anti-competitive practices in the payment exclusivity system of Shopee from the perspective of Islamic banking management. The research focuses on the exclusivity policy of payment methods implemented within digital platform ecosystems and its implications for business competition and the principles of justice in Islamic economics. This study employs a qualitative method using a Systematic Literature Review (SLR) approach by collecting, selecting, and analyzing relevant academic literature, regulations, journals, and previous studies related to digital payment systems, business competition, and Islamic banking management. The findings indicate that there is an exclusivity element within Shopee’s payment system that limits the use of certain payment methods in transactions. Such practice potentially affects openness in digital payment market access and creates barriers for other financial service providers. From the perspective of Islamic banking management, this exclusivity system should be critically reviewed based on the principles of justice (al-‘adl), balance, transparency, and fair competition in order to support a more inclusive transaction ecosystem and prevent market dominance. This study is expected to contribute academically to discussions on digital business competition and the development of payment systems aligned with sharia principles.